Numerical Computation for Modified Cross Model Fluid Flow Around the Circular Cylinder with Symmetric Trapezoidal Cavities - Mahmood, Rashid; Siddique, Imran; Khan, Ilyas; Badran, Mohamed; Mehrez, Sadok; Majeed, Afraz Hussain; Naaz, Sehrish (Frontiers in Physics, 2022)
The study of modified cross model (MCM) fluid flow around the circular obstacle with symmetric trapezoidal cavity isinvestigated by numerical computing. Momentum equation elucidating the flowing features of (MCM) has been solved by implementing finite element method (FEM) for range of: power law index (m) 0 to 5, Reynold number is fix for Re=20 and modified parameter (b) from 0.0 to 0.5. Domain discretization at coarse level is performed by ( 21 PP ) shape functions. In addition, (MCM) fluid considers parabolic profile for inlet velocity also the Neumann condition is placed at outlet of channel. Circular obstacle is placed at (2, 1) middle of symmetric cavities. Fluid forces like drag and lift variations are measured, also evaluates the line velocity profile for different values of m at several positions.